2018
DOI: 10.1002/jmr.2712
|View full text |Cite
|
Sign up to set email alerts
|

The binding interaction between cadmium‐based, aqueous‐phase quantum dots with Candida rugosa lipase

Abstract: As a promising biolabeling biomaterials, quantum dots (QDs) present a great potential. However, the toxicity of QDs to organisms has attracted wide attention. In our research, we introduced an in vitro method to study the molecular mechanisms for the structure and activity alterations of Candida rugosa lipase (CRL) with the binding of 3-mercaptopropionic acid-capped CdTe QDs. Multiple spectroscopic methods, isothermal titration calorimetry, and enzyme activity measurements were used in this paper. QDs statical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…Figure 6 shows the activity of enzyme in the presence and absence Enzymatic activity is a very complex process and depends on several factors. The interaction of MPAcapped CdSe QDs with α-amylase results in loss of secondary structure of α-amylase which could be the possible reason of inhibition of enzymatic activity; it is in accordance with previous studies which reported the similar kind of result (Sun et al 2014;Zhao et al 2018). Although the loss in secondary structure was maximum with the MPA-capped CdSe QDs of the largest size (3.9 nm), inhibition of enzymatic activity is found to be maximum with MPA-capped CdSe QDs of the smallest size 1.9 nm followed by 2.3 nm, 2.5 nm, 3.3 nm, and 3.5 nm.…”
Section: Effect On Enzymatic Activitysupporting
confidence: 92%
See 1 more Smart Citation
“…Figure 6 shows the activity of enzyme in the presence and absence Enzymatic activity is a very complex process and depends on several factors. The interaction of MPAcapped CdSe QDs with α-amylase results in loss of secondary structure of α-amylase which could be the possible reason of inhibition of enzymatic activity; it is in accordance with previous studies which reported the similar kind of result (Sun et al 2014;Zhao et al 2018). Although the loss in secondary structure was maximum with the MPA-capped CdSe QDs of the largest size (3.9 nm), inhibition of enzymatic activity is found to be maximum with MPA-capped CdSe QDs of the smallest size 1.9 nm followed by 2.3 nm, 2.5 nm, 3.3 nm, and 3.5 nm.…”
Section: Effect On Enzymatic Activitysupporting
confidence: 92%
“…The results obtained from molecular docking show that hydrogen bonding and hydrophobic interactions are involved in interaction of MPA with α-amylase; however hydrophobic interaction is found as major force of interaction. Experimental results obtained by Das et al (2016) and Zhao et al (2018) also suggested the hydrophobic interaction as major force of interaction in water-soluble MPA-capped cadmium-based QDs with enzyme lysozyme and candida rugosa lipase (CRL), respectively (Das et al 2016;Zhao et al 2018). It was further indicated that MPA have not interacted directly with the catalytic and substrate binding active site of α-amylase, hence acted as non-competitive inhibitor (Zheng et al 2020).…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Generally, proteins have two major absorption bands, which are the strong absorption peak at 210 nm reflecting polypeptide backbone structure of the protein and the weak absorption peak at 280 nm illustrating the transformation of chromophore microenvironment . Upon the gradual addition of maltol to CAT solution, the absorption intensity of the peak at 210 nm decreased significantly, which could reflect the transition of π → π* of the polypeptide backbone structure and the change of CAT skeleton structure . No significant changes of the peak at 280 nm were observed with changes in the concentration of maltol, indicating maltol have no influence on the transformation of CAT chromophores …”
Section: Resultsmentioning
confidence: 99%
“…Hydrolyzed triglyceride is con-verted into Glycerin and fatty acids are absorbed by the body [6] and play an important role in the process of digestion and absorption. Zhao Lining et al [7] studied the interaction of three mercaptopropionic acid-terminated CdTe quantum dots with lipase, and proved that three mercaptopropionic acid-terminated CdTe quantum dots can cause toxic side effects on lipase; Zhang Rui et al [8] studied the interaction of bisphenol A with lipase in vitro to better understand the toxicity and toxicity mechanism of bisphenol A.…”
Section: Figure 1 Chemical Structure Of Mobicmentioning
confidence: 99%